The effectiveness of Snoezelen as multisensory intervention among individual who exhibit maladaptive behaviour/ Shahrizal Selamat ... [et al.] - Selamat, Shahrizal; Amiruddin, Aliff; Dahlan, Akehsan; Kadar, Masne (Faculty of Health Sciences, Universiti Teknologi MARA, 2019)
Snoezelen has been implemented to children, adults and elderly with disabilities. It provides multisensory environment that allows individual to select and received sensory input in desirable types and amount. A systematic approach to evaluating the evidence of effectiveness of Snoezelen towards individuals with maladaptive behavior is needed. Studies investigating the effectiveness of Snoezelen were systematically searched for using standardized keywords across five databases. The initial search identified 2300 references. From these articles, five met the inclusion criteria and were subject to full methodological appraisal. One study was primarily qualitative and four studies primarily quantitative design. Studies were appraised using McMaster critical appraisal tools and data were extracted and synthesized. The finding from this synthesis review were summarized narratively which was based on the research question, inclusion criteria and outcome reported. Most of the studies demonstrate a low impact of the Snoezelen on the maladaptive behavior. Maladaptive behavior will occur after Snoezelen is terminated and the effects is not generalized to other setting. Overall, the findings from this systematic review indicate that there was a main concern on the usage of Snoezelen as intervention and the impact of the intervention itself toward the sample of the studies.